2000
DOI: 10.1080/03601230009373271
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long‐term pesticide applications on some soil biological parameters

Abstract: The soil oxidative and anaerobic processes, as well as, the microbial biomass were followed during three years in a cotton farm (Tatuí) where the recommended pesticides have been used for several years, and in an experimental field (São Paulo) treated first time with the same pesticides. The oxidative process was monitored by the dehydrogenase (DHA)-activity using triphenyltetrazolium chloride (TTC) as substrate. The anaerobic process was followed by the iron-oxide reduction, and the microbial biomass was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…Several studies have reported the adaptation of soil microflora to IPU degradation in response to repeated exposure to this herbicide over a long period on fields under cultivation El-Sebai et al 2005). The IPU degrading ability of soil microflora has been found to be influenced by various soil and environmental factors (Aislabie and Lloydjones 1995;Andrea et al 2000;Bending et al 2003;El-Sebai et al 2007), among which pH is considered to be a key factor affecting biodegradation not only in isolated cultures Hussain et al 2009;Sun et al 2009) but also in soils (Houot et al 2000;El-Sebai et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have reported the adaptation of soil microflora to IPU degradation in response to repeated exposure to this herbicide over a long period on fields under cultivation El-Sebai et al 2005). The IPU degrading ability of soil microflora has been found to be influenced by various soil and environmental factors (Aislabie and Lloydjones 1995;Andrea et al 2000;Bending et al 2003;El-Sebai et al 2007), among which pH is considered to be a key factor affecting biodegradation not only in isolated cultures Hussain et al 2009;Sun et al 2009) but also in soils (Houot et al 2000;El-Sebai et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…However, the indiscriminate and extensive use of pesticides represents one of the major environmental and public health problems all over the world [1,2]. If improperly used, pesticides can lead to secondary pest outbreaks [3], destruction of non-target species [4], soil, water, and air contamination [5,6], and residues in primary and derived agricultural products [7] that endanger both the environment and human health. Farm workers’ exposure to pesticides has been associated with adverse health effects like cancer and birth defects resulting in hundreds of fatalities, the majority of which occur in developing countries [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most living organisms do not have this enzyme, which is however, ubiquitous in microorganisms (Busse et al, 2001). The amount and diversity of soil microorganisms are extremely important for soil metabolic processes, because they act on the organic matter decomposition contributing for the soil fertility (Bromilow et al, 1996;Andréa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%